Biomassa proveniente da casca da banana Musa sapientum: análise do potencial energético para produção de bioetanol - Moura, Isaac Anderson Alves de (2019)
In a scenario of population growth and enrichment in developing countries, the demand for food and energy has become a challenge for large production and consumption centers, which reinforces the need for alternative, clean and renewable sources of energy, where, for example, the use of biomass fits perfectly into the context of sustainable development. In this sense, the scope of this study is to verify the technical feasibility of using biomass energy from silver banana peel residues for bioethanol generation. The banana peel was collected and subjected to drying, grinding, sieving, physicochemical characterization, acid hydrolysis using sulfuric acid (H2SO4), fermentation with Saccharomyces cerevisiae and distillation. This study determined the percentage of 41.02 ± 0.015% peel per fruit. The study material was subjected to suspension soluble solids test before and after acid hydrolysis, presenting in natura 8.5% SSS. As for hydrolyzate, the tests were performed using 0.5, 1.0 and 1.5 moles of sulfuric acid, in which 17, 22 and 28% of soluble solids were observed respectively. The hydrolyzate was submitted to the reducing sugars (AR) test using 0.5, 1.0 and 1.5 moles of sulfuric acid, where it was found 29.74, 7.73 and 8.24 mg / mL in that order. In the alcoholic fermentation with Saccharomyces cerevisiae the best conditions for ethanol production were: Culture medium B2 (cultivation with addition of molasses) followed by media B3 and B1 with the values for reducing sugars consumed 61.96, 20.76 and 14, 72 g / l respectively. At the end, obtaining the alcohol content of the delined wine, being B2 5.7, B3 1.7 and B2 1.2 ºGL. Regarding the ethanol yield (Yp / s) for the tests B1, B2 and B3 were 0.64, 0.75 and 0.65 (g.g), higher yield values than those obtained by other researchers for different banana varieties. The hydroalcoholic solution resulting from distillation presented the following values related to the alcohol content: B1 69.26 ºGL, B2 29.47 ºGL and B3 22.55 ºGL. These results reached parameters for proper distillation. Thus, it can be said that all results were satisfactory, since it was possible to obtain ethanol in all tests. At first it is probable to produce bioethanol from the banana crop residues (peel), presenting as an alternative in biofuel production, without the need to increase the sugarcane cultivated area, avoiding to compete directly with food production. Therefore, the development of this study is potentially relevant for increasing research on renewable energy